Chitosan intercalated metal organic gel as a green precursor of fe entrenched and fe distributed N-doped mesoporous graphitic carbon for oxygen reduction reaction - Shijina, Kottarathil; Illathvalappil, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Yamaguchi, Takeo; Anilkumar, Gopinathan M.; Hareesh, U. S.; Sailaja, G. S. (Chemistryselect, 2017)
Herein, we present Metal-Organic Gel intercalated with chitosan, a `green'' precursor for the synthesis of intrinsic N-doped Fe entrenched (CHI-TMA-Fe-CW) and Fe distributed mesoporous graphitic carbon structures (CHI-TMA-Fe-CW-M1) with appreciable Oxygen Reduction Reaction (ORR) activity in alkaline medium. Modulation of the synthetic protocol as a function of reaction kinetics and gelation time while maintaining identical pyrolysis conditions (900 degrees C, flowing N-2 atmosphere) improves the microstructure, surface area and Fe distribution of the graphitic structures (CHI-TMA-Fe-CW-M1). CHI-TMA-Fe-CW has a Fe entrenched graphitic nanocapsule like morphology while Fe distributed mesoporous graphitic carbon sheets, with a specific surface area value of 565 m(2) g(-1) obtained by modulating the synthesis chemistry in CHI-TMA-Fe-CW-M1. The higher percentage of graphitic N in CHI-TMA-Fe-CW-M1 apparent from the XPS data validate that the modified synthetic method favours creation of more graphitic N sites contributing for better catalytic performance. CHI-TMA-Fe-CW-M1 catalyst exhibited comparable electrocatalytic activity with that of the commercially available Pt/C via an efficient four-electron-dominant ORR pathway with a positive onset potential value of 0.925 V vs RHE. Good durability of CHI-TMA-Fe-CW-M1 after 5000 cycles further confirm the prospects of MOG-chitosan and the feasibility to be used as a potential catalyst for ORR.
Keywords: electrocatalyst; fuel cell; Metal-Organic-Gel; oxygen reduction reaction

Melamine formaldehyde-metal organic gel interpenetrating polymer network derived intrinsic Fe-N-doped porous graphitic carbon electrocatalysts for oxygen reduction reaction - Shijina, Kottarathil; llathvalappil, Rajith; Sumitha, N. S.; Sailaja, G. S.; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Anilkumar, Gopinathan M.; Yamaguchig, Takeo; Hareesh, U. S. (New Journal of Chemistry, 2018)
Fe, N doped porous graphitic carbon electrocatalyst (Fe-MOG-MF-C), obtained by pyrolysis of an Interpenetrating Polymer Network (IPN) comprised of melamine formaldehyde (MF as hard segment) and Metal-Organic Gel (MOG as soft segment), exhibited significant Oxygen Reduction Reaction (ORR) activity in alkaline medium. BET surface area analysis of Fe-MOG-MF-C showed high surface area (821 m(2) g(-1)), while TEM, Raman and XPS results confirmed Fe and N co-doping. Furthermore, a modulated porous morphology with a higher degree of surface area (950 m(2) g(-1)) has been accomplished for the system (Fe-MOG-MFN-C) when aided by a sublimable porogen, such as naphthalene. XPS results further demonstrated that these systems exhibited a better degree of distribution of graphitic N and an onset potential value of 0.91 V vs. RHE in 0.1 M KOH solution following an efficient four-electron ORR pathway. The electrocatalytic activity of Fe-MOG-MFN-C is superior to that of Fe-MOG-MF-C by virtue of its higher graphitic N content and surface area. Thus, the study presents a new class of IPN derived MF-MOG nanocomposites with the potential to generate extended versions of in situ Fe-N doped porous graphitic carbon structures with superior ORR activity.

Morphological ensembles of N-doped porous carbon derived from ZIF-8/Fe-graphene nanocomposites: processing and electrocatalytic studies - Thomas, Minju; Illathvalappil, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Anilkumar, Gopinathan M.; Yamaguchi, Takeo; Hareesh, U. S. (ChemistrySelect, 2018)
Engineering the active site density of porous carbon catalysts for enhanced electrocatalytic activity is the current focus in the quest for economically viable fuel cells. Herein, we synthesise ZIF-8/Fe-graphene composites for the formation of N and Fe co-doped carbon with diverse morphologies ranging from tubes and sheets to frameworks of carbon. A synthetic strategy involving the one pot synthesis of ZIF-8 based composites is accomplished by the reaction of 2-methylimidazole with mixed Zn/Fe salt solution containing graphene dispersions. The high temperature heat treatment of this precursor mix yielded micro-meso porous architectures of N, Fe co-doped carbon with dispersions of Fe/Fe3C. An onset potential value of 0.95 V and a half-wave potential of 0.82 V coupled with excellent durability and stability in alkaline medium indicated improved electrocatalytic performances over its commercial Pt/C counterpart. The appreciable electrocatalytic properties of the synthesized carbon are attributed to its morphological diversity, hybrid structure, high N doping and its heteroporous characteristics. The dispersed Fe/Fe3C and FeNx sites facilitated enhanced oxygen adsorption and the graphene inclusions in the composite provided retention of high nitrogen contents.
Keywords: electrocatalyst; fuel cell; N- Fe co-doped carbon; oxygen reduction reaction; ZIF-8

Template assisted synthesis of Ni,N co-doped porous carbon from Ni incorporated ZIF-8 frameworks for electrocatalytic oxygen reduction reaction - Priya K., Vaishna; Thomas, Minju; Illathvalappil, Rajith; K., Shijina; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Anilkumar, Gopinathan M.; Yamaguchi, Takeo; Hareesh, U. S. (New Journal of Chemistry, 2020)
A heteroatom doped porous carbon electrocatalyst with enhanced oxygen reduction reaction (ORR) performance in alkaline medium was obtained by high temperature treatment of Ni incorporated ZIF-8 frameworks and its composite with g-C(3)N(4)as a supporting matrix template. The morphology and porosity of this heteroatom containing carbon were tuned by varying the Ni : Zn molar ratio in Ni/Zn ZIF-8 and Ni/Zn ZIF-8@g-C(3)N(4)composites. The template aided synthetic strategy using g-C(3)N(4)helped in the controlled decomposition of composites leading to a heteroporous sheet like architecture with increased nitrogen content. The Ni/Zn ZIF-8 sample on heat treatment in the 800-1000 degrees C temperature range led to the formation of Ni,N co-doped porous carbon (Ni-NPC) with Ni-C active sites. The defective sites induced by nickel carbide along with the distributed N atoms on the carbon surface enabled active O(2)adsorption sites. The high surface area, high degree of graphitisation as well as the defects created by well dispersed N and Ni on porous carbon matrices favoured charge separation leading to higher electrochemical ORR activity. The Ni,N co-doped carbon catalyst in alkaline medium exhibited a limiting current density of 5.2 mA cm(-2)with a half-wave potential of 0.76 Vvs.RHE in 0.1 M KOH. The catalyst also showed improved methanol tolerance and better stability compared to the standard Pt/C catalyst.

Hydrophilic 3D interconnected network of bacterial nanocellulose/black titania photothermal foams as an efficient interfacial solar evaporator - Nabeela, Kallayi; Thorat, Meghana; Sumina, N. B.; Ramachandran, Animesh M.; Thomas, Reny Thankam; Preethikumar, Gopika; Mohamed, A. Peer; Asok, Adersh; Dastager, Syed Gulam; Pillai, Saju (ACS Applied Bio Materials, 2021)
The design and development of scalable, efficient photothermal evaporator systems that reduce microplastic pollution are highly desirable. Herein, a sustainable bacterial nanocellulose (BNC)-based self-floating bilayer photothermal foam (PTF<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">b) is designed that eases the effective confinement of solar light for efficient freshwater production via interfacial heating. The sandwich nanoarchitectured porous bilayer solar evaporator consists of a top solar-harvesting blackbody layer composed of broad-spectrum active black titania (BT) nanoparticles embedded in the BNC matrix and a thick bottom layer of pristine BNC for agile thermal management, the efficient wicking of bulk water, and staying afloat. A decisive advantage of the BNC network is that it enables the fabrication of a lightweight photothermal foam with reduced thermal conductivity and high wet strength. Additionally, the hydrophilic three-dimensional (3D) interconnected porous network of BNC contributes to the fast evaporation of water under ambient solar conditions with reduced vaporization enthalpy by virtue of intermediated water generated via a BNC–water interaction. The fabricated PTF<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">b is found to yield a water evaporation efficiency of 84.3% (under 1054 W m<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2) with 4 wt % BT loading. Furthermore, scalable PTF<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">b realized a water production rate of 1.26 L m<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–2 h<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">–1 under real-time conditions. The developed eco-friendly BNC-supported BT foams could be used in applications such as solar desalination, contaminated water purification, extraction of water from moisture, etc., and thus could address one of the major present-day global concerns of drinking water scarcity.

Co-incorporated N-doped micro-meso porous carbon as an electrocatalyst for oxygen reduction reaction and Zn-air battery - Priya, Vaishna K.; Kharabe, Geeta Pandurang; Barik, Sidharth; Mohamed, A. Peer; Kurungot, Sreekumar; Hareesh, Unnikrishnan Nair Saraswathy (Energy and Fuels, 2024)
Metal-organic frameworks are considered ideal precursors for the preparation of transition-metal, heteroatom-doped carbon catalysts that are perceived to be efficient electrocatalysts for energy storage devices. Herein, we demonstrate the synthesis of ZIF-67-derived Co-incorporated N-doped porous carbon catalysts supported on high surface area microporous carbon prepared from a lotus seed shell. The combination of the two carbon catalysts in different weight ratios resulted in Co-incorporated N-doped carbon sheets with tuned surface area and porosity, enabling enhanced oxygen reduction reaction (ORR) activity in an alkaline medium. The optimized carbon catalyst ZL 600 (3:1) exhibited a half-wave potential of 0.79 V vs RHE and a limiting current density of -4.38 mA cm(-2) in 0.1 M KOH solution with higher stability and methanol tolerance. The optimized sample ZL 600 (3:1) demonstrated as a cathode in a zinc-air battery exhibited an open circuit voltage of 1.29 V with a flat discharge profile at a current rate of 10 mA cm(-2). The homemade system produced a specific capacity of 610 mAh g(-1) and a peak power density of 111 mW cm(-2), comparable to the cathode made with Pt/C. The high micro-mesoporosity, pyridinic and pyrrolic nitrogen contents, as well as enriched Co-active centers protected by carbon sheets favorably contributed to the efficient ORR mechanism.